RELIGION, CHURCH, INTIMATE CITIZENSHIP AND GENDER EQUALITY - Mieke Verlo (SCAD Independent, 2015)
During the past decades, processes of (post)modernization have raised the importance of quality-of-life issues and related policies, resulting in a higher salience of intimate citizenship issues on the political agenda. The Catholic Church as an institution especially has been articulating strong positions on issues considered to be about personal and family morality, actively opposing liberalization of abortion or even contraception, assisted reproduction for non-married couples, and the extension of marriage rights to homosexual people. This paper will investigate to what extent the framing of a number of intimate citizenship issues (reproductive rights, abortion, same-sex marriage and divorce) by the Catholic Church resonates with the framing of these issues in Catholic countries that are members or candidate to the European Union, and whether the presence or absence of resonance is linked to the degree of religiosity of the population, the support for Catholic religious values or to the institutional strength of the Catholic Church. The analysis will show to what extent we find ‘Catholic’ frames in the various countries and how that is connected to the level of religiosity, the support for Catholic religious values or the institutional strength of the Catholic Church.